Analysis of a Steerable Needle for Fine Needle Aspiration and Biopsy: Efficiency and Radiation Dose Compared With a Conventional Straight Needle. Issue 6 (November 2017) - Rutigliano, Sandra; Abraham, John A.; Kenneally, Barry E.; Zoga, Adam C.; Nevalainen, Mika; Roedl, Johannes B.
Abstract : Purpose: Percutaneous computed tomography (CT)–guided needle biopsy has proven to be an efficacious method for sampling of many soft tissue lesions, especially deep-seated masses in the abdomen and pelvis. This study sought to test the potential for a novel steerable needle to improve localization and to reduce procedure duration and radiation dose compared with a conventional straight needle. Material and Methods: A fresh, raw meat sample (lean bovine flank) was imbedded with cylindrical radiopaque and radiolucent obstacles designed to simulate vessels (radiolucent objects) and bones (radiopaque objects) on CT. A pit-containing olive (partially radiopaque) was imbedded beyond the obstacles to represent the target. Two sites on the surface of the meat were selected and marked to determine initial needle placement. Two radiologists with different levels of experience proceeded to position a straight needle and the steerable needle from each skin site to the target using CT guidance as efficiently as possible, avoiding the obstacles. The total positioning time, the number of CT scans required for positioning, and the number of repositioning events (partial withdrawal followed by advancement) were tracked for the straight and steerable needles. Results: For the straight needle, total time to reach the target was 499 to 667 seconds (mean, 592 seconds); for the steerable needle, total time to reach the target was 281 to 343 seconds (mean, 309 seconds), on average, 48% lower. The number of CT scans needed for needle positioning averaged 6.25 for the straight needle and 3.5 for the steerable needle, which is 44% lower. Repositioning events (withdrawing and readvancing the needle) ranged from 3 to 10 for the straight needle (mean, 6.5) and 0 for the steerable needle. Conclusions: Using an in vitro model embedded with obstacles, the steerable needle performed better than a straight needle with regard to procedure time, needle repositioning events, and CT scans required for placement.